2004
DOI: 10.3168/jds.s0022-0302(04)73245-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Milk Urea and Production, Nutrition, and Fertility Traits in Israeli Dairy Herds

Abstract: The objectives of this study were to identify and evaluate production and environmental factors that influence milk urea (MU) in Israeli dairy herds, to analyze the relationships between MU concentration and nutritional variables, and to examine a possible association between MU and pregnancy rate (PR). Production and environmental data were obtained from the Israeli Dairy Herd Improvement (DHI) Center (n = 1,279,600). Programmed total mixed rations (feeds and quantities) on milk-test day were collected from 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
76
6
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(113 citation statements)
references
References 15 publications
23
76
6
8
Order By: Relevance
“…Moreover, the new crop maize silage included in the ration in the fall could be a reason for the high herd deviant percentage. This assumption is supported by Hojman et al (2004), who studied the relationship between groups of rations fed to milking cows and test-day mean herd MUN concentrations. They found a significant relationship for the feed group "summer crop harvested as silage," which included maize and sorghum.…”
Section: Target Range At the Herd Levelmentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, the new crop maize silage included in the ration in the fall could be a reason for the high herd deviant percentage. This assumption is supported by Hojman et al (2004), who studied the relationship between groups of rations fed to milking cows and test-day mean herd MUN concentrations. They found a significant relationship for the feed group "summer crop harvested as silage," which included maize and sorghum.…”
Section: Target Range At the Herd Levelmentioning
confidence: 56%
“…These studies have shown that MU is related mostly to the dietary CP (Broderick and Clayton, 1997;Hojman et al, 2004;Nousiainen et al, 2004) or to the surplus of nitrogen that is available in the rumen for microbial growth compared with the available energy (RDP balance, or OEB in the Dutch and Belgian standard; Hof et al, 1997;Schepers and Meijer, 1998;Frand et al, 2003). Moreover, MU concentrations are related to individual production traits, such as test-day production of milk, fat, or protein.…”
Section: Introductionmentioning
confidence: 99%
“…Hypotheses suggest that a high urea concentration impairs reproduction through an indirect effect on the energy status (Broderic and Clayton, 1997). Hojman et al (2004) reported increase in the levels of MU was negatively related to reproductive performance of dairy cows. An excessive intake of degradable protein and a relative shortage of energy to synthesize bacterial proteins will result in the accumulation of excessive ammonia in the rumen, which is absorbed through the ruminal wall and converted into urea in the liver.…”
Section: Genetic and Phenotypic Correlationsmentioning
confidence: 91%
“…Many authors (Aguilar et al, 2012;Biswajit et al, 2011;Geerts et al, 2004;Hojman et al, 2004;Oltner et al, 1985) are of the opinion that, for dairy cows, the level of urea in cow's milk (MU, milk urea) may be the indicator of whether the energy balance and protein ratio are proper. In general, in properly balanced feed, the MU ratio is at 15-30 mg dL −1 .…”
Section: Introductionmentioning
confidence: 99%